Analisis komparatif pengaruh retrofitting refrigeran HCFC:R22 konversi HC:MC22 pada mesin refrigerasi kompresi uap single stage - Triana, Aji; Biantoro, Agung Wahyudi (Journal of New Energies and Manufacturing, 2022)
Each refrigerant can affect the different refrigeration and performance coefficients, from previous research has published. Until now, there are still many users of HCFC: R22 refrigerants in air conditioning systems, so research is continuing to make a refrigerant that can replace HCFC: R22 refrigerants, HC: MC-22 refrigerants can replace HCFC: R22 synthetic refrigerants. This study aims to see the effect on the use of these refrigerants through retrofitting on refrigeration machines of the type of unit AC-Split which are expected to measure the performance, energy consumption and cooling rate of these types of refrigerants, as well as to determine the type of refrigerant. The results showed that the compressor discharge pressure had a significant effect on performance / COP (Coefficient of Performance) with the average obtained for the use of refrigerant R22 of 6.61 and MC22 of 7.54. Then there is a significant effect on energy consumption with the average obtained by using R22 refrigerant of 131.1 Wꞏh and MC22 of 115.7 Wꞏh, while there is no significant effect on the rate of cooling in door (evaporator temperature) with an average obtained when using R22 is 22.71 °C and MC22 is 21.77 °C. In the 60th minute, the COP obtained by refrigerant R22 is 5.8 and MC22 is 7.1, then consume the energy used by the refrigerant R22 264.0 Wꞏh and MC22 of 231.0 Wꞏh and temperature measurement in door (evaporator) refrigerant R22 at 20.20 °C and MC22 at 19.90 °C.